Syllabus of Plant Families. A. Engler’s Syllabus der Pflanzenfamilien, 13th edition. Part 2/1: Photoautotrophic Eukaryotic Algae. Glaucocystophyta, Cryptophyta, Dinophyta/Dinozoa, Haptophyta, Heterokontophyta/Ochrophyta, Chlorarachniophyta/ Cercozoa - Mann, David G. (Edinburgh Journal of Botany, 2017)
..